The World Stroke Organization future leaders program: building leadership capacity in global stroke care - Carbonera, Leonardo; de Souza, Ana Cláudia; Lioutas, Vasileios-Arsenios; Minhas, Jatinder S.; Sebastian, Ivy; Nasreldein, Ahmed; Shapranova, Julia; Markus, Hugh; Chen, Christopher; Hacke, Werner; Caso, Valeria (International journal of stroke, 2025)
BACKGROUND: Leadership development is essential to advancing stroke care globally. The World Stroke Organization (WSO) Future Stroke Leaders Program (FSLP) was established to identify and support global early-career professionals in stroke care worldwide. The program offers structured leadership training, mentorship, and seed funding for implementation projects. Selection criteria prioritize diversity, leadership potential, and institutional support. The article describes the design and implementation of the WSO FSLP and evaluates its contribution to stroke care advancement, professional development, and global collaboration. - METHODS: This is a descriptive narrative of the WSO FSLP, based on program documentation, participant surveys, and public databases. Programmatic key performance indicators (KPIs) aligned with WSO's strategic goals were used to track impact. - RESULTS: Among 56 participants in the first two cohorts, selected from over 35 countries, engagement with the WSO FSLP contributed to improved access to and delivery of care by developing stroke services in underserved areas, enhancing publication output, and supporting active involvement in international policy and advocacy efforts. Participants reported career advancement, increased research engagement, and expanded collaborative networks as a direct result of their participation in the program. - CONCLUSIONS: The WSO FSLP is a model for developing global stroke leadership. Its impact spans clinical innovation, academic research, and policy influence, guiding implementation. Continued program adaptation to the changing international landscape, alumni engagement, and long-term impact evaluation will help sustain and scale worldwide contributions to stroke care equity.
Online veröffentlicht: September 26, 2025$y(2025), online ahead of print
Gesehen am 19.11.2025